Aproximación conceptual a la empatía - Sebastián Capó, Jaume (Revista de Psicoterapia, 2003)
In this article, Jaume Sebastián Capó talks about the concept of empathy, its etymology, psychological origin, definition, and how it relates to the concepts of perception, sensitivity, projection and affective participation.